Effects of Cerrado restoration on seasonal soil hydrological properties and insights on impacts of deforestation and climate change scenarios - Pereira, Luara Castilho; Balbinot, Leonardo; Nnadi, Ernest O.; Mosleh, Mojan Hadi; Tonello, Kelly Cristina (Frontiers in Forests and Global Change, 2022)
Knowing soil indicators during forest restoration is essentially better for understanding the recovery of ecosystem functions for water conservation. The aim of the study is to assess seasonal changes in hydrological properties of sandy soils subjected to passive restoration for 8 (F8), 11 (F11) and 46 (F46) years in Cerrado. The herein assessed soils present the same land use history and climate conditions. The soil density (SD), moisture (SM), organic matter (SOM), resistance to penetration (SRP) and infiltration rate (IR) were measured for 12 months and repellency index (RI) was obtained in the dry season. Some annual soil hydrological property differences based on passive restoration sites were observed, but differences in other properties were only noticed through seasonality analyses. Higher SM, IR and K values were recorded in the rainy season and higher SRP values were observed in the dry season. IR was approximately 4-fold higher in F8 and 3-fold higher in F11 and F46 in the rainy season, than in the dry season. IR was higher in the older stand and lower (by over 60%) in the youngest restoration site, which also showed higher RI. Thus, significant differences in several hydrological soil properties and forest restoration soils subjected to the assessed chrono-sequence helped to confirm the study hypothesis, namely: these properties are influenced by forest age and are a warning against deforestation and climate change scenarios. The recovery of hydrological properties can be a slow process, much slower than deforestation rates, and it can have severe implications because soil water inflow is related to groundwater maintenance. So, the role of these properties helps to develop a sustainable land management, and better and more efficient soil conservation strategies for sites undergoing passive restoration such as Cerrado.